The Influence Of Price And Product Quality On Consumer Purchase Intention At Umkm Ayam Geprek Buk Effa In Tanjung Agung Village, Pagar Gunung District, Lahat Regency - Rinaldi Febriansyah; Iskandar Iskandar; Hayani Hayani (Universitas Dehasen Bengkulu, 2026)
The purpose of this study was to determine the effect of price and product quality on consumer purchasing interest at the Buk Effa Fried Chicken MSME in Tanjung Agung Village, Pagar Gunung District, Lahat Regency. The variables in this study were price (X1), product quality (X2), and purchasing interest (Y). The data analysis methods used were instrument testing (reliability testing, validity testing), classical assumption testing (normality testing, heteroscedasticity testing, multicollinearity testing), multiple linear regression analysis, hypothesis testing (t-test and F-test), and coefficient of determination testing. The results of the study showed that (1) price has a significant partial effect on purchasing interest, as evidenced by the calculated t value > t-table (6.900 > 1.987). (2) product quality has a significant partial effect on purchasing interest, as evidenced by the calculated t value > t-table (3.337 > 1.987). (3) Price and Product Quality have a significant simultaneous effect on Purchase Intention, as seen from the calculated f value > f table (57.770 > 3.953), and the significance value is smaller than the significance level (a) of 0.05 (0.000 < 0.05).